Effects of Mulberry Pomace Addition and Transglutaminase Treatment on the Quality of Pasta Enriched with Antioxidants and Dietary Fiber - Thi Minh Ngoc Ta; Chi Hieu Hoang; Thao Mi Nguyen; Thi Thu Tra Tran; Nu Minh Nguyet Ton; Le Van Viet Man (Polish Journal of Food and Nutrition Sciences)
Mulberry pomace powder, a by-product of mulberry juice processing, was added to pasta recipe to make pasta with high dietary fiber and antioxidant contents. The effects of mulberry pomace ratio on the nutritional, textural and cooking properties as well as the sensory overall acceptance of the product were investigated. A significant increment in dietary fiber and total anthocyanin contents as well as decrement in cooking quality, texture and color change were observed. The cooking loss increased with the substitution level of mulberry pomace while the optimal cooking time, swelling index and water absorption index decreased. The quality improvement of 10% mulberry pomace fortified pasta was investigated by adding a transglutaminase preparation with enzyme dosage from 0.25 to 1.00 U/g protein. The fortified pasta treated with transglutaminase at 0.50 U/g protein showed a significant improvement in chewiness, tensile strength and elongation rate but was not significantly affected in terms of the swelling index and water absorption. The use of transglutaminase also improved the overall acceptability of the fortified pasta. Mulberry pomace powder may, therefore, be considered a potential antioxidant-rich and dietary fiber-rich material for incorporation into pasta products.